Reduction of reverse leakage current at the TiO₂/GaN interface in field plate Ni/Au/-GaN Schottky diodes - Shashikala, B.N.; Nagabhushana, B.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
This paper presents the fabrication procedure of a TiO₂ passivated field plate Schottky diode and gives a comparison of Ni/Au/-GaN Schottky barrier diodes without a field plate and with a field plate of varying diameters from 50 to 300 µm. The influence of field oxide (TiO₂) on the leakage current of Ni/Au/-GaN Schottky diode was investigated. This suggests that the TiO₂ passivated structure reduces the reverse leakage current of the Ni/Au/-GaN Schottky diode. Also, the reverse leakage current of Ni/Au/-GaN Schottky diodes decreases as the field plate length increases. The temperature-dependent electrical characteristics of TiO₂ passivated field plate Ni/Au/-GaN Schottky diodes have shown an increase of barrier height within the temperature range 300…475 K. Наведено процедуру виготовлення діода Шотткі з охоронним кільцем з пасивуючим шаром TiO₂, а також порівняно бар’єрні діоди Шотткі Ni/Au/-GaN без охоронного кільця та з ним різних діаметрів від 50 до 300 мкм. Досліджено вплив пасивуючого оксиду (TiO₂) на струм витоку у діоді Шотткі Ni/Au/-GaN. Це свідчить про те, що пасивуюча TiO₂ структура зменшує зворотний струм витоку у діоді Шотткі Ni/Au/-GaN. Також зворотний струм витоку у діодах Шотткі Ni/Au/n-GaN зменшується із збільшенням розмірів охоронного кільця. Температурно-залежні електричні характеристики діодів Шотткі Ni/Au/n-GaN з охоронним кільцем з пасивуючим шаром TiO₂ показали збільшення висоти бар’єра в діапазоні температур 300–475 K.